Rodent models of ischemic stroke lack translational relevance… are baboon models the answer?. (May 2014) - Kwiecien, Timothy D.; Sy, Christopher; Ding, Yuchuan
<x content-type="archive" xml:space="preserve">Abstract</x> Rodent models of ischemic stroke are associated with many issues and limitations, which greatly diminish the translational potential of these studies. Recent studies demonstrate that significant differences exist between rodent and human ischemic stroke. These differences include the physical characteristics of the stroke, as well as changes in the subsequent inflammatory and molecular pathways following the acute ischemic insult. Non-human primate (NHP) models of ischemic stroke, however, are much more similar to humans. In addition to evident anatomical similarities, the physiological responses that NHPs experience during ischemic stroke are much more applicable to the human condition and thus make it an attractive model for future research. The baboon ischemic stroke model, in particular, has been studied extensively in comparison to other NHP models. Here we discuss the major shortcomings associated with rodent ischemic stroke models and provide a comparative overview of baboon ischemic stroke models. Studies have shown that baboons, although more difficult to obtain and handle, are more representative of ischemic events in humans and may have greater translational potential that can offset these deficiencies. There remain critical issues within these baboon stroke studies that need to be addressed in future investigations. The most critical issue revolves around the size and the variability of baboon ischemic stroke. Compared to rodent models, however, issues such as these can be addressed in future studies. Importantly, baboon models avoid many drawbacks associated with rodent models including vascular variability and inconsistent inflammatory responses – issues that are inherent to the species and cannot be avoided.